The impact of scale and frass recirculation on pathogen inactivation dynamics in black soldier fly larvae bioconversion - Lalander, Cecilia; Lopes, Ivã Guidini; Gyftopoulos, Nikos; Vinnerås, Björn (Frontiers in Microbiology, 2025)
A promising waste management technology that has emerged within the past decade is bioconversion of waste with the larvae of the black soldier fly (BSFL). Regarding waste management purposes, hygiene is central. At present, most studies on BSFL conversion have been performed in small-scale laboratory settings, and the mechanisms behind the documented inactivation of microorganisms remain unclear. In this study, the inactivation dynamics of pathogens and indicator organisms during BSFL bioconversion of food waste was investigated. Two trials were conducted: one mimicking a large-scale industrial setup and another evaluating the impact of frass recirculation on pathogen reduction to better understand the potential role of bioactive compounds in frass. The results indicate that pathogen inactivation observed in small-scale setups is also applicable to large-scale systems, with no significant scale impact on inactivation. The primary difference between scales was increased water evaporation in larger systems, leading to higher electrical conductivity in the frass. Increased solid retention time through frass recirculation did not significantly affect pathogen inactivation but considerably improved the yield of larvae per treated tonne of food waste. The results clearly show that inactivation is linked to larval presence and activity. However, the specific mechanisms driving this effect remain unclear—whether due to bioactive compounds produced by the larvae, physico-chemical changes induced by their activity, or a combination of both. Future research should focus on the microbial risks associated with long-term frass recirculation and further explore the balance between biological and chemical inactivation factors.